2002
DOI: 10.1001/archopht.120.6.722
|View full text |Cite
|
Sign up to set email alerts
|

Phototherapeutic Keratectomy for Anterior Basement Membrane Dystrophy After Laser In Situ Keratomileusis

Abstract: To evaluate the efficacy and safety of phototherapeutic keratectomy (PTK) in the treatment of symptomatic anterior basement membrane dystrophy following laser in situ keratomileusis (LASIK). Methods: In a retrospective study, 10 eyes of 10 patients that developed symptomatic anterior basement membrane dystrophy following LASIK for myopia were treated with PTK using the VISX S2 (VISX Inc, Santa Clara, Calif) excimer laser. Primary outcome measurements including corneal clarity, resolution of symptoms, uncorrect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
(24 reference statements)
0
10
0
Order By: Relevance
“…It is therefore important to conduct a thorough examination to identify signs of EBMD based on corneal morphology in the absence of RCE. 26,27 In PTK treated eyes, epithelial removal was performed with a laser in 22 cases (42%) where the epithelium was smooth, similar to the method reported by Dinh et al 8 While there are a few reports of laser epithelial removal prior to PTK for EBMD, 5,6,8,24,28 the number of patients in these studies was small and the effect of epithelial removal method on outcome could not be examined. In this study, we found a borderline-significant trend towards a greater chance of recurrence with laser epithelial removal.…”
Section: Discussionmentioning
confidence: 96%
“…It is therefore important to conduct a thorough examination to identify signs of EBMD based on corneal morphology in the absence of RCE. 26,27 In PTK treated eyes, epithelial removal was performed with a laser in 22 cases (42%) where the epithelium was smooth, similar to the method reported by Dinh et al 8 While there are a few reports of laser epithelial removal prior to PTK for EBMD, 5,6,8,24,28 the number of patients in these studies was small and the effect of epithelial removal method on outcome could not be examined. In this study, we found a borderline-significant trend towards a greater chance of recurrence with laser epithelial removal.…”
Section: Discussionmentioning
confidence: 96%
“…Excimer laser PTK has been performed successfully to treat recurrent corneal erosions refractory to conservative treatment, even after LASIK, [24][25][26] with a recurrence-free rate of 46% to 100% after one procedure. 19,20 However, several authors report they do not consider PTK after LASIK because PTK can produce a mild hyperopic shift.…”
Section: Discussionmentioning
confidence: 99%
“…Phototherapeutic keratectomy has been used successfully to manage flap striae 22 and other LASIK flap complications, 23 but only a few studies 24,25 have reported the results of PTK to treat recurrent corneal erosions after LASIK, and all procedures were performed at least 3 months after LASIK. Because the presence of recurrent corneal erosions in the immediate post-LASIK period is highly symptomatic, we performed PTK early in the postoperative period, ie, 1 month after LASIK.…”
mentioning
confidence: 99%
“…Postoperatively, they may develop symptoms of recurrent erosions, slit-lamp microscopic fi ndings of epithelial basement membrane degeneration, irregular astigmatism, and decreased PTK for Residual Refractive Error After LASIK/Faktorovich & Nosova visual acuity. 12,13 They may also have postoperative refractive error. Typically, a patient who is unsatisfi ed with the refractive error after LASIK is considered for an additional laser treatment to try to achieve the desired outcome.…”
Section: Discussionmentioning
confidence: 99%
“…They also noted a mean hyperopic shift after PTK. 13 Phototherapeutic keratectomy has been reported to result in refractive change in eyes without previous refractive surgery as well. 7,[14][15][16][17][18][19] Although the effect of PTK on refractive error is variable, there is an overall tendency toward a small hyperopic shift.…”
Section: Discussionmentioning
confidence: 99%